The role of acetylides in dual gold catalysis: a mechanistic investigation of the selectivity difference in the naphthalene synthesis from diynes - Graf, Katharina; Hindenberg, Philip; Tokimizu, Yusuke; Naoe, Saori; Rudolph, Matthias; Rominger, Frank; Ohno, Hiroaki; Hashmi, A. Stephen K. (ChemCatChem, 2014)
Under the conditions of dual activation catalysis with oxygen nucleophiles, β-substituted naphthalenes were obtained from 1,2-diethinyl arenes. Mechanistic studies, which include isotope labeling experiments, support that dual activation leads to β-substituted naphthalenes, whereas α-naphthalenes are formed by π activation only, and no gold acetylide or dual activation is involved in the formation of the α-substituted products. Additional experiments on substrates that led to dibenzopentalenes support these mechanistic insights.